Penerapan Model Problem Based Learning (PBL) terhadap Kemampuan Berpikir Kritis dan Bekerja Sama Peserta Didik pada Mata Pelajaran Fikih MA Al-Kautsar Pekanbaru - Awwalul 'Abidin; Hidayati Hidayati; Rivdya Eliza (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Agama Islam Nahdlatul Wathan Samawa Sumbawa Besar, 2025)
This study is motivated by the low levels of critical thinking and collaboration skills among eleventh-grade students at MA Al-Kautsar Pekanbaru, which have negatively affected their learning outcomes in Fiqh. The learning process has been predominantly teacher-centered with one-way interactions, minimal material analysis, and a lack of group collaboration. The objective of this research is to describe the implementation of the Problem-Based Learning (PBL) model in enhancing students' critical thinking and collaboration skills. The study employed a quasi-experimental method using a randomized control group only design. The sample consisted of class XI-A (25 students) as the experimental group taught using the PBL model, and class XI-B (32 students) as the control group taught using conventional methods. Data collection techniques included tests, questionnaires, and observations. The results showed that: (1) the average critical thinking score of students in the experimental group was 84.00, higher than the control group’s 62.66, with a t-value of 10.247 > t-table value of 2.004; and (2) the average collaboration skill score in the experimental group was 81.56, compared to 64.88 in the control group, with a t-value of 5.359 > t-table value of 2.004. In conclusion, the PBL model is effective in improving students' critical thinking and collaboration skills in Fiqh learning.Keywords: Problem-Based Learning, critical thinking skills, student collaboration, Fiqh.